Penyusunan Alat Pengukur Berbasis Theory of Planned Behavior - Neila Ramdhani (Faculty of Psychology Universitas Gadjah Mada, 2011)
One of theories to which researcher aiming to test people’s attitudes and behaviors always refer isthe Theory of Planned Behavior (TPB). It has been developed from the Theory of Reasoned Action(TRA) as a response to criticism about the inconsistent relationship between attitude and behavior.To overcome this weakness, antecedent behaviors are developed in more specific way both in termsof concept and measurement. This paper aims to provide a description of how to set the aitems ofmeasuring instruments based on the TPB. Some notes about the way of presenting the measuringinstruments and the stages are depicted in the end of this paper.